Characteristics, controls and geological models of hydrocarbon accumulation in the Carboniferous volcanic reservoirs of the Chunfeng Oilfield, Junggar Basin, northwestern China. (June 2018) - Wang, Yong; Yang, Renchao; Song, Mingshui; Lenhardt, Nils; Wang, Xinzheng; Zhang, Xuecai; Yang, Shaochun; Wang, Jun; Cao, Haifang
Abstract: The Junggar Basin is one of the most important basins for hydrocarbon production in China. Within the basin, the Chunfeng Oilfield forms one of the most important oilfields of the area. Despite the significant work that has been done on the rocks of the oilfield so far, a detailed reservoir characterization and description of the hydrocarbon accumulation pattern was still missing. Therefore, an investigation had been initiated to fill this gap in our understanding of the hydrocarbon reservoirs of the Junggar Basin. The results of this study show that the tuff and andesitic lava lithofacies exhibit the highest reservoir potential in the area. Apart from the lithofacies, the results of this study show that tectonic (formation of fault systems) and diagenetic (formation of solution pores) effects, and the development of a weathering crust are crucial factors that control the quality of the petroleum reservoirs of the oilfield. In addition, two possible geological models of petroleum accumulation in isolated volcanic rocks and sandstone (IVRS) and connected volcanic rocks and sandstone (CVRS) are presented. Highlights: Tuff and andesitic lava lithofacies exhibit the highest reservoir potential. Tectonic and diagenetic controls on the quality of the volcanic rock reservoirs. Two possible geological models of petroleum accumulation in volcanic rock reservoirs.